KINERJA PELAYANAN PEMERIKSAAN KAPAL BERBENDERA INDONESIA OLEH MARINE INSPECTOR - Euis Saribanon; Reza Fauzi Jaya Sakti (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
Tanjung Priok Harbormaster Office is a unit at the Sea General Directorate in the Ministry of Transportation. This unit has a task to carry out surveillance and law enforcement in shipping. To know the service performance of vessel inspection, the Public Satisfaction Index is used, due to PAN Ministerial Decree No. KEP-25 / M.PAN / 2/2004 on 24th February 2004 concerning on the Guidelines of Public Satisfaction Index in the Service Unit of the Government Agency. This study aims to analyze the service performance of Indonesian vessel inspection by the Marine Inspector to the level of Public Satisfaction Index at the Tanjung Priok Harbormaster Office Jakarta. The result of the study shows that 1 from 14 indicators measured is still not good, which is the accuracy of time in vessel inspection. This means that the organization has less competency in recruiting the Marine Inspectors or Marine Inspector Candidates. The organization also lacks of facilities and infrastructures to support the activities of vessel inspection, resulting the user dissatisfaction at the Tanjung Priok Harbormaster Office.